Exploitation of natural resources and the low-carbon switching of techniques inside linear production schemes - Gianmarco Oro (PSL Quarterly Review, 2023)
The present work investigates the links between Ricardian and Sraffian economic analyses and the emerging themes of ecological macroeconomics, namely the impact of global warming and ecological or natural crises, the depletion of non-produced material resources, and the energy transition. The objectives of the work are: (a) to introduce the foundations of ecological economics through a simple representation of Ricardo's economic theory of the falling rate of profit (i.e., the stationary state), explaining the socio-economic impact of ecological crises linked to production process (global warming, land pollution, flooding, etc.) and of the shrinkages in the supply (extraction) of non-produced factors like energy materials (oil, coal, liquefied natural gas, etc.); (b) to evaluate the institutional conditions that must be met to make the energy transition from fossil fuels to renewable resources economically meaningful when capital accumulation is the main driver of economic growth; and (c) to broaden the field of research and perspectives within heterodox approaches to ecological macroeconomics by introducing new foundations based on modern Classical political economy.
Keywords: B51; E11; Q57; 330; ecological crises; embodied energy; exhaustible resources; low-carbon energy transition